(3ahGFO CHj jYdi GdNdjdi Hf YHO Gddg Hf CMeO GdNdjdi GdMGaXs - (3GHf YeQ GdOjQjs
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe CHh MaU YeQ Yf GHf CHj edjcg Yf YGFTI QVi Gddg YfgG bGdJ (B: (3Kbd QShd Gddg Udi Gddg Ydjg hSde bGd dYHO GdQMef Hf CHj HcQ CJjfi HdhM CcJH dCHi HcQ cJGHkG dGjNJda Ydjg s
(3BNQgG (B:s
(3MOKfG eMeO Hf eMeO Hf gGQhf Hf GdMLGL bGd QCjJ SajGf GdKhQi SGLOkG Hecg Mhd GdHjJ aWaJ SHYI CSGHjY bHd Cf jQaY QCSg BNQ GdLRA hGdMeO ddg QH GdYGdejf s
(3YdjgG NW GHf eadM GdMfHdi HUMI GdSeGY hGdELGRI s
(3HChdgG hBNQgG SeGYGJ YOjOIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(803) s
Keywords: (3GdMOjK h GdeUWdMs